Plant Stress Granules: Trends and Beyond - Maruri-López, Israel; Figueroa, Nicolás E.; Hernández-Sánchez, Itzell E.; Chodasiewicz, Monika (Frontiers in Plant Science, 2021)
Stress granules (SGs) are dynamic membrane-less condensates transiently assembled through liquid-liquid phase separation (LLPS) in response to stress. SGs display a biphasic architecture constituted of core and shell phases. The core is a conserved SG fraction fundamental for its assembly and consists primarily of proteins with intrinsically disordered regions and RNA-binding domains, along with translational-related proteins. The shell fraction contains specific SG components that differ among species, cell type, and developmental stage and might include metabolic enzymes, receptors, transcription factors, untranslated mRNAs, and small molecules. SGs assembly positively correlates with stalled translation associated with stress responses playing a pivotal role during the adaptive cellular response, post-stress recovery, signaling, and metabolic rewire. After stress, SG disassembly releases mRNA and proteins to the cytoplasm to reactivate translation and reassume cell growth and development. However, under severe stress conditions or aberrant cellular behavior, SG dynamics are severely disturbed, affecting cellular homeostasis and leading to cell death in the most critical cases. The majority of research on SGs has focused on yeast and mammals as model organism. Nevertheless, the study of plant SGs has attracted attention in the last few years. Genetics studies and adapted techniques from other non-plant models, such as affinity capture coupled with multi-omics analyses have enriched our understanding of SG composition in plants. Despite these efforts, the investigation of plant SGs is still an emerging field in plant biology research. In this review, we compile and discuss the accumulated progress of plant SGs regarding their composition, organization, dynamics, regulation, and their relation to other cytoplasmic foci. Lastly, we will explore the possible connections among the most exciting findings of SGs from mammalian, yeast, and plants, which might help provide a complete view of the biology of plant SGs in the future.